Introduction of Quantum System, Step Potential and Barrier Potential to Class X Students of SMA Budi Utomo Bengkulu City - Syafitri, Dini; Dari, Anggen; Setiawan, Iwan; Matrasulov, Jasur (Aktual: Jurnal Pengabdian Kepada Masyarakat, 2024)
Physics is a science that is very close to everyday life. However, physics learning is often a subject that is less attractive to students because it tends to be difficult to understand. This community service aims to introduce and provide an understanding of physics, especially quantum systems, including potential steps and potential barriers to students of SMA Budi Utomo Kota Bengkulu. Activities are carried out in 3 stages namely preparation, implementation, and evaluation stages. The community service method used in this study was socialization and material exposure with PPT instruments. The research was aimed at class X students with a total of 31 students at SMA Budi Utomo Kota Bengkulu.  Implementation This service activity was carried out in November 2023. The results showed that students can understand abstract physics material using simple language and examples in everyday life. It can be concluded that students will more easily understand abstract physics material if it is delivered effectively and involves active learning activities.